2022
DOI: 10.3390/ijms23179950
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MADS-Box Transcription Factors in Iris laevigata and Functional Assessment of IlSEP3 and IlSVP during Flowering

Abstract: Iris laevigata is ideal for gardening and landscaping in northeast China because of its beautiful flowers and strong cold resistance. However, the short length of flowering time (2 days for individual flowers) greatly limits its applications. Molecular breeding and engineering hold high potential for producing I. laevigata of desirable flowering properties. A prerequisite is to identify and characterize key flowering control genes, the identity of which remains largely unknown in I. laevigata due to the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The MADS-box genes are involved in regulating many biological processes, such as seed germination ( He et al, 2019 ), vegetative growth ( Cohen et al, 2012 ), floral organ specification ( Kong et al, 2022 ), flowering ( Liu et al, 2022 ), embryo and fruit development ( Colombo et al, 2008 ; Pi et al, 2021 ). At present, most of the floral organ development-related genes belong to the MADS-box family.…”
Section: Introductionmentioning
confidence: 99%
“…The MADS-box genes are involved in regulating many biological processes, such as seed germination ( He et al, 2019 ), vegetative growth ( Cohen et al, 2012 ), floral organ specification ( Kong et al, 2022 ), flowering ( Liu et al, 2022 ), embryo and fruit development ( Colombo et al, 2008 ; Pi et al, 2021 ). At present, most of the floral organ development-related genes belong to the MADS-box family.…”
Section: Introductionmentioning
confidence: 99%
“…I. laevigata is native to northeast China with strong cold resistance and beautiful flowers of unique shape and bright color [26]. Such desirable traits make I. laevigata a good candidate for both landscaping and industrial use as a cutting flower.…”
Section: Introductionmentioning
confidence: 99%
“…Such desirable traits make I. laevigata a good candidate for both landscaping and industrial use as a cutting flower. However, the potential is dampened because of the short flowering period with only 2 days for a single flower and 20 days for the population [26]. To stagger the flowering time and prolong the flowering period, it is necessary to find genes that can advance or delay the flowering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested the role of type I MADS-box genes in the regulation of endosperm development in Arabidopsis and grasses [ 9 , 10 , 11 ]. Similarly, MIKC-type members of MADS-box have been widely studied for their ability to form transcription factor complexes and their vital role in the control of flowering development [ 12 , 13 , 14 ]. According to the widely used ABCDE model of flower organ development, class A genes participate in sepal development in the first whorl; then, class A, B (AP3 and PI), and E (AGL3 and SEP) genes collectively control the petal identity in the second whorl, while class B, C (AG), and E genes all together control the stamen identity in the third whorl.…”
Section: Introductionmentioning
confidence: 99%